Single dose oral zinc as adjuvant therapy in children admitted with severe pneumonia: A randomized, placebo-controlled study - Basavraj, G V; Nijaguna, N; Gembeeran, Raja; Sanjeeva, G N (Indian Journal of Child Health, 2016)
Background: Childhood pneumonia is one of the major causes of under-five mortality in developing countries. Any interventions which can reduce the mortality and morbidity of pneumonia are of great importance. Adjuvant zinc therapy is one such intervention studied in various parts of the world with inconclusive results. Objective: We aim to study the impact of a single dose of zinc therapy on the outcome of childhood severe pneumonia. Material and Methods: Randomized, placebo-controlled study of young children between 2 and 24 months was conducted to study the impact of single dose zinc administration on time to resolution of severe pneumonia. The subjects were assigned two groups, zinc group and non-zinc group, by stratified randomization. The zinc group received unlabeled oral zinc syrup 20 mg of elemental zinc as single dose for children >6 months of age and 10 mg of elemental zinc as single dose for children <6 months. The non-zinc group children were administered unlabeled non-zinc containing placebo as single dose. Results: From April 2011 to December 2011, 1284 children screened for pneumonia as per Integrated Management of Neonatal and Childhood Illnesses guidelines and 126 children were included in the study. Of these 126 children, 63 were randomized to receive zinc and 63 to receive placebo. The mean duration of respiratory distress before hospitalization was 1.4±0.5 days in zinc group as compared to 1.1±0.5 days in non-zinc group (p=0.001). The mean duration of resolution of distress was 52.47±33.99 h in zinc group as compared to 74.17±37.76 h in the non-zinc group (p=0.05). Similarly, the mean duration for resolution of symptoms was 65.52±36.03 h in zinc group as compared to 88.00±37.97 in non-zinc group (p=0.05). The 23% of the children in non-zinc group had treatment failure (p=0.03). Conclusion: Single dose of adjuvant oral zinc therapy in severe pneumonia, reduces the duration of respiratory distress, resolves the symptoms early and decreases the incidence of treatment failure. However, the total duration of hospitalization was not affected by zinc therapy.